Span Morphing Using the Compliant Spar - Saavedra-Flores, E (American Society of Civil Engineers, 2015)
This paper develops and models the compliant spar concept that allows the wingspan to be varied to provide roll control and enhance the operational performance for a medium altitude, long endurance (MALE) UAV. The wing semispan is split into morphing partitions and the concept may be incorporated in each partition; however, only the tip partition is considered here. The compliant spar is made of compliant joints arranged in series to allow the partition to be flexible under axial (spanwise) loads, but at the same time stiff enough to resist bending loads. Each compliant joint consists of two concentric overlapping AL 2024-T3 tubes joined together using elastomeric material. Under axial (spanwise) loading, the elastomeric material deforms in shear, allowing the overlapping distance between the tubes to vary and hence the length (in the spanwise direction) of the joint/spar to vary. High fidelity modeling of the concept is performed. Then, structural design optimization studies are performed to minimize the axial stiffness and the structural mass of the concept for various design constraints. The flexible skin and actuation system to be used are also addressed. © 2014 American Society of Civil Engineers.